Analisis Pengaruh Likuiditas, Leverage, Profitabilitas, Market Value, dan Free Cash Flow terhadap Peringkat Obligasi dengan di Mediasi oleh Manajemen Laba - Setiawati, Eka; Tanjung, Amries Rusli; Indrawati, Novita (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2019)
This study aims to find empirical evidence of the effect of liquidity, leverage, profitability, free cash flow and market value on bond ratings mediated by earnings management. This research was conducted at 60 banking companies registered in Pefindo Indonesia in 2015-2017. The sampling technique in this study used a purposive sampling technique and data analysis techniques used the Path Analysis method with the SPSS versi 22 application.The results of this study conclude: (1) There is an influence between Liquidity, Leverage, Profitability, and Free Cash flow to earnings management. (2) There is no effect of Market Value on earnings management. (3) The influence of Liquidity, Leverage, Profitability and Free Cash flow on Bond Rankings is mediated by Profit Management. (4) The absence of influence between Market Value on bond ratings is mediated by earnings management.